Evaluation of water dynamics and protein changes in bigeye tuna (Thunnus obesus) during cold storage - Wang, Xin-Yun; Xie, Jing (Food science & technology, 2019)
The objective of this study was to investigate water dynamics and protein changes in bigeye tuna (Thunnus obesus) stored at 0 °C and 4 °C for up to 6 days. The values of various protein parameters (trichloroacetic acid (TCA)-soluble peptide content, Ca2+-ATPase enzyme activity and total -SH content) decreased with increasing storage time. Fourier transform infrared spectra indicated that the secondary structure of the proteins changed; the contents of α-helixes and β-turns significantly decreased, while that of β-sheets significantly increased (p < 0.05). Atomic force microscopy and sodium dodecyl sulfate-polyacrylamide gel electrophoresis results revealed that the length, diameter and height of the myofibril proteins decreased significantly and that myosin and actin degraded during cold storage. The results of low-field nuclear magnetic resonance (LF-NMR) spectroscopy showed that T21 (trapped water) was positively correlated (p < 0.01) with water-holding capacity (WHC), Ca2+-ATPase activity, and the total contents of -SH groups, ionic bonds, hydrogen bonds, α-helixes and random coils. In addition, T21 was negatively correlated (p < 0.01) with the contents of TCA-soluble peptides, hydrophobic interactions, disulfide bonds and β-sheets. Therefore, the correlation between water dynamics and protein changes was successfully shown and can be used to monitor changes in the quality of bigeye tuna during cold storage. •Water migration and protein changes in bigeye tuna (Thunnus obesus) at 0 °C and 4 °C.•T21 correlated with protein parameters.•LF-NMR and FT-IR can be used to monitor dynamic quality changes.